Efficient Raman generation in a hydrogen-filled hollow-core fibre. (September 2015) - Gladyshev, A.V.; Kolyadin, A.N.; Kosolapov, A.F.; Yatsenko, Yu.P.; Pryamikov, A.D.; Biriukov, A.S.; Bufetov, I.A.; Dianov, E.M.
Abstract: Efficient Raman generation in a molecular hydrogen-filled hollow-core fibre having a cladding in the form of a single ring of capillaries has been demonstrated for the first time. The pump source used was a -switched Nd : YAG laser with a pulse duration of, and a single-pass (cavity-free) configuration was employed. The maximum average output power at was, and the differential quantum efficiency was 87 %, a record level for such experiments.